Invasion-mediated changes in the population biology of a dimorphic whitefish Coregonus lavaretus population - Bøhn, Thomas; Amundsen, Per-Arne (Finnish Zoological and Botanical Publishing Board, 2004)
Source at https://www.jstor.org/publisher/fzb . Population biology changes in native dimorphic whitefish Coregonus lavaretus were studied over a decade in the subarctic Pasvik watercourse, where large biotric changes occurred due to an invasion by vendace C. albula . Although initially recorded in the upstream part of the watercourse, where it is now the dominant pelagic species, the vendace subsequently also colonised the downstream area. We hypothesized that the impact of the invader would affect the population biology (density, habitat choice, growth, size- and age-structure and size and age at maturation) of the native whitefish populations, especially upstream in the watercourse, late in the invasion phase, and in the pelagic whitefish morph. Strong effects from the invading vendace were observed on the native dimorphic whitefish populations. Effects on the densely-rakered white-fish, which are ecologically similar to vendace, ranged from numerical responses (strong density decline in the population), habitat use (shift from pelagic to littoral) and indivudual growth (significant growth reduction in zooplanktivorous life stages). For the benthic sparsely-rakered whitefish, effects were more restricted and recorded mainly on growth.